Roles of palmitoylation and the KIKK membrane-targeting motif in leukemogenesis by oncogenic KRAS4A - Zhao, Huanbin (J Hematol Oncol, 2015)
BACKGROUND: We have previously shown that palmitoylation is essential for NRAS leukemogenesis, suggesting that targeting RAS palmitoylation may be an effective therapy for NRAS-related cancers. For KRAS-driven cancer, although much research has been focused on the KRAS4B splice variant, which does not undergo palmitoylation, KRAS4A has recently been shown to play an essential role in the development of carcinogen-induced lung cancer in mice and to be widely expressed in human cancers. However, the role of palmitoylation in KRAS4A tumorigenesis is not clear. METHODS: The expression of KRAS4A in KRAS-mutated leukemia cell lines and acute myeloid leukemia (AML) cells were checked using western blotting and reverse transcriptions-quantitative polymerase chain reaction (RT-qPCR) analysis, respectively. The leukemogenic potentials of oncogenic KRAS4A and its palmitoylation-defective mutants were examined by a mouse bone marrow transduction and transplantation model and the in vitro transformation assays. The activation of the RAS downstream signaling pathways and the membrane localizations of the KRAS4A and its mutants were analyzed via western blot analysis and confocal microscopy, respectively. RESULTS: We show here that KRAS4A is expressed in human leukemia cell lines and in AML cells harboring KRAS mutations and that mutation at the palmitoylation site of oncogenic KRAS4A significantly abrogates its leukemogenic potential. However, unlike NRAS, palmitoylation-defective KRAS4A still induces leukemia in mice, albeit with a much longer latency. Using NRAS/KRAS4A chimeric constructs, we found that the KIKK motif of KRAS4A contributes to the transforming activity of KRAS4A. Mutations at both palmitoylation site and the KIKK motif abolish the ability of oncogenic KRAS4A to induce leukemia in mice. CONCLUSIONS: Our studies suggest that therapies targeting RAS palmitoylation may also be effective in treating KRAS4A associated malignancies and that interfering the KIKK membrane-targeting motif would enhance the therapeutic effectiveness.